Réus e vítimas : criminalidade, justiça e cotidiano em uma região de imigração alemã (São Leopoldo, 1846-1871) - Mühlen, Caroline von (2017)
The following research has as its goal the analysis of the social profile of the actors involved in disputes, the reasons that lead to lawsuits, the strategies used to settle the differences and the everyday experiences or the social behavior of those individuals who had to explain themselves to the local justice system during the second half of the 19th century. The purpose of this thesis is to demonstrate that the "social organization" of Germans, both descendants and nationals, in the Village and City of São Leopoldo, was marked by countless tensions, claims, misunderstandings and conflicts both inside the group and outside of it. The starting point of the research is 1846, the year of the passage from Capela Curada [a chapel with a resident priest] to Village, and the resulting structuration of its own political, administrative and juridical apparatus. The time span of the research ends in 1871, when the law number 2.033, the Criminal Lawsuit Code, was approved, that is, before the Township became a County, in 1875, the end of the Paraguay War (1864-1870) and the Mucker conflict (1873-1874). By analyzing the lawsuits present to the Grand Jury, we realized that the questions that motivated the use of violence were not directly related to political party aspects, but instead they were based on disputes and misunderstandings related to economic and sociocultural issues. Thus, the violence led to justice practice used by several individuals in order to settle down disagreements, mostly during the historical agents' leisure time at the grocery store, during a public ball or even during a horse race, but also in disputes for land and in recurring problems deriving from properties' measurements and invasions.